(untitled) (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to explore the effects of motherwort alkaloids on rat ear acne. The rats that were administered high, medium, and low doses of motherwort alkaloids, tanshinone capsules, a model and a control group. Each group of rats was subjected to gavage once daily for 14 consecutive days. On the first day of testing, the control and model groups were administered an intradermal auricle injection of sterilized saline solution and the remaining groups were administered an intradermal auricle injection of Staphylococcus epidermidis in addition to the gavage. The thicknesses of the rats auricles were measured for five consecutive days following the injections. Anticoagulated blood was used for erythrocyte rheology index measurement. In addition, the entire ear of each rat was removed for morphological examination. Compared to the model group, the group administered motherwort alkaloids exhibited significantly reduced swelling, improved localized auricle proliferation, and reduced blood viscosity. This result suggests motherwort alkaloids are effective in rat ear acne.